Association of human resource maintenance and development programs and intention to stay of managers in selected fast food restaurants in Metro Manila - Yuliati, Lilik Noor; Lopez, Ma. Belinda V. (1998)
The importance of human resource management in the business world will remain as long as human motivation continues to be a complex, mysterious and yet wonderful phenomenon that baffle and dazzle bosses, administrators, and scholars alike. This study is an attempt to comprehend why and how managers would choose to remain in his or her position, and for how long, given so many internal and external pull and push factors in the workplace and professional environment. It seeks to contribute to enhancing the satisfaction of managers and the corporation, and in the long run, better human resource management. This study assumes that prior to entering and while staying in the fast food company, managers have relatively common environment such as Human Resource(HR) maintenance and development programs. HR maintenance program can come in the form of salary, benefit package, performance appraisal, treatment of supervisor, and work environment, while human resource development programs can be provided through training and career development. The study tested the association between HR maintenance and development programs and the managers' intention to stay and their intended duration of stay in the company given their characteristics such as age, gender educational attainment, work experience, position classification, present tenure, salary rate and work hour. The three fastfood companies, McDonald's, Pizza Hut, and Shakey's, were chosen from among the top ten of the 146 restaurants corporations on SEC list of the 5,000 Best Sellers in the Philippines in 1995, who were willing to participate in the study. This descriptive study used the Alpha-Z score procedure to select sample respondents. Three groups of managers such as store manager, assistant manager, and management trainee of 64 stores, were selected from among comparable managerial positions in the three fast food companies in Metro Manila. Data gathering was done during the months of October to December 1997. The researcher and three assistants distributed the three copies of questionnaire with a permission letter from companies to each selected store. Retrieval was conducted based on the appointment to pick up those questionnaires. Data from questionnaires were organized, analyzed, and interpreted using SPSS/PC+ program to perform descriptive statistical analyses managers' characteristics. Logistic, as well as multiple regression analyses on the other hand were utilized to discern the significance of relationship among variables. Findings show that all but a very few managers, generally aged 20-30 years old, of balanced gender composition, working for one to five years in the same company, who are already experienced in the foodservice business, do intend to remain in their current company. Almost half of the respondents signified their intention to stay for the next five years or even longer. In a nutshell, the study empirically identified factors that retain managers. These are work compensation, additional benefits, performance appreciation, agreement of performance standards, solving interpersonal problems, and the clarity of the company's vision and mission to the managers. In terms of intended duration of stay, the factors indicated were pay structure, fairness of and satisfaction regarding benefit packages, performance feedback, appreciation of good performance, matching of skills and abilities with responsibility, maintaining open communication, reasonableness of work hours and schedule, satisfaction of work environment and opportunities open to managers to contributing ideas. Training and career development appear to be the most determining variable for staying while low salary and limited career development bring to fore the dire motivation to leave. The respondents signified positive perception toward all HR maintenance and development variables, except the external competitiveness with their salaries. These indicate that the companies have relatively good HR maintenance and development programs. The characteristics of the managers themselves showed no significant relationship with their intention to stay and their intended duration of stay. Among the dimensions under study, only position classification found among management trainees exhibited positive relationship with regard to intention to stay.
"March 2008."
Thesis (M. Food Service Administration)--University of the Philippines Diliman.
Keywords: Fast food restaurants -- Philippines -- Manila Metropolotian Area